Answer:
<u>Has the form y = kx</u>
( y = 0.11x)
(y = 0.04x)
<u>Can be put into form y = kx</u>
(z/x = 9)
<u>Other</u>
(5 = xy)
( x = y/2)
Step-by-step explanation:
<u>y = kx</u>
( y = 0.11x)
(y = 0.04x)
<u>kx = y</u>
(z/x = 9)
-----------
( x = y/2 )
( x - 5 = y)
(5 = xy)
Answer:
The answer is c.
Step-by-step explanation:
-5x + 5 > 160 - 10x
5x > 155
x > 31
Answer:
No, because the curve indicates that the rate of
change is not constant.
Im 99.9 sure
Step-by-step explanation:
1 8/4 so you add them and get yo answer then make it into a improper fraction
Answer: x = -2
Step-by-step explanation:
-x + 4x = x - 4
=> 3x = x - 4
=> 3x - x = -4
=> 2x = -4
=> x = -2